2008
DOI: 10.1007/s11240-008-9402-0
|View full text |Cite
|
Sign up to set email alerts
|

Generation of marker free salt tolerant transgenic plants of Arabidopsis thaliana using the gly I gene and cre gene under inducible promoters

Abstract: Despite the advances in transgenesis, transformation technologies still rely on the introduction of a selectable marker gene to identify cells and tissues that have integrated the gene of interest in their genome. The continuous presence of the marker genes in the transgenics is often controversial as it can potentially have multiple undesirable impacts. The present study employed the self-excising Cre-loxP system to generate marker-free Arabidopsis thaliana expressing the agronomically important glyoxalase I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…The deduced TcGLX1 polypeptide was compared with Gly I and TaGly I from B. juncea and T. aestivum, respectively, which have been used to increase Zn tolerance (Singla-Pareek et al 2006;Lin et al 2010) and Zn accumulation (Singla-Pareek et al 2006) in tobacco. While the deduced polypeptide sequence of T. caerulescens GLX1 shows high identity with the polypeptide in B. rapa and ATGLX1 in A. thaliana (90-92%), the identity with T. aestivum TaGly I is 74% (Lin et al 2010) and with B. juncea Gly I only 22-23% (Veena et al 1999;SinglaPareek et al 2003SinglaPareek et al , 2006Bhomkar et al 2008;Roy et al 2008). The Gly I polypeptide of B. juncea is short, the deduced molecular mass being ca.…”
Section: Discussionmentioning
confidence: 99%
“…The deduced TcGLX1 polypeptide was compared with Gly I and TaGly I from B. juncea and T. aestivum, respectively, which have been used to increase Zn tolerance (Singla-Pareek et al 2006;Lin et al 2010) and Zn accumulation (Singla-Pareek et al 2006) in tobacco. While the deduced polypeptide sequence of T. caerulescens GLX1 shows high identity with the polypeptide in B. rapa and ATGLX1 in A. thaliana (90-92%), the identity with T. aestivum TaGly I is 74% (Lin et al 2010) and with B. juncea Gly I only 22-23% (Veena et al 1999;SinglaPareek et al 2003SinglaPareek et al , 2006Bhomkar et al 2008;Roy et al 2008). The Gly I polypeptide of B. juncea is short, the deduced molecular mass being ca.…”
Section: Discussionmentioning
confidence: 99%
“…A number of genes orthologous to those we have isolated from S. stapfianus have been successfully utilised to enhance drought or salt or cold tolerance in model plants or important crop species. These include glyoxylase1, catalase, cysteine protease, several group 2 and group 3 LEAs, aquaporins, a myb transcription factor and the translation initiation factor eIF1 (Mohamed et al 2003;Villalobos et al 2004;Sheokand et al 2005;Brini et al 2007;Cui et al 2008;Diédhiou et al 2008;Roy et al 2008;Wang et al 2009a). Approaches to using genes associated with desiccation tolerance for improving drought tolerance in crop species have recently been reviewed by Toldi et al (2009) and Moore et al (2008b).…”
Section: Isolation Of Desiccation-tolerance Specific Genesmentioning
confidence: 99%
“…Although previous studies have reported the best performance of constitutive promoters in regulating the glyoxalase pathway gene(s) during abiotic stress conditions, data regarding the performance of the same during unstressed conditions are missing. A few studies have been conducted using stress-inducible ''responsive to desiccation'' (rd29A) gene promoter to regulate the expression of gly I gene in transgenic plants (Rajwanshi et al 2007;Roy et al 2008). Previous studies have shown that rd29A and rd29B genes are induced under high temperature, high salt, and drought or with exogenous abscisic acid (ABA) treatment due to the presence of drought-responsive element (DRE) and ABA-responsive element (ABRE) Shinozaki 1993, 1994;Bihmidine et al 2013).…”
Section: Introductionmentioning
confidence: 99%